Aspartyl proteinase, phospholipase, esterase and hemolysin activities of clinical isolates of the Candida parapsilosis species complex. (April 2013) - Treviño-Rangel, Rogelio de J.; González, J. Gerardo; González, Gloria M.
<x xml:space="preserve">Abstract</x> Candida parapsilosis is considered as an important emerging fungal pathogen and was recently found to be a complex that include three species, i.e., Candida parapsilosis sensu stricto, Candida orthopsilosis and Candida metapsilosis. The aim of this study was to determine the in vitro aspartyl proteinase, phospholipase, esterase and hemolysin activities of 65 clinical isolates of the C. parapsilosis complex, which had been previously identified by RFLP-BanI analysis. Of the enzymes evaluated, aspartyl proteinase was the least produced by the C. parapsilosis species complex. Phospholipase and esterase were strongly expressed by C. orthopsilosis (67% of isolates), while 10% and 13% of C. parapsilosis sensu stricto isolates were strong producers, respectively, of these two enzymes. In contrast, high production of both enzymes was not detected in C. metapsilosis. Hemolysin activity was significantly more abundant in C. orthopsilosis (87%) than C. parapsilosis sensu stricto (67%). Overall, C. orthopsilosis isolates were statistically associated with the production of hemolysins (P = 0.048) and phospholipases (P < 0.0001) compared to isolates of C. parapsilosis sensu stricto or C. metapsilosis. Furthermore, a statistical association was found between isolates recovered from blood and phospholipase production (P = 0.017). The distribution of isolates obtained from blood was 30% of C. parapsilosis sensu stricto, 67% of C. orthopsilosis and 20% of C. metapsilosis.